DECISION-MAKING METHOD FOR MULTIMEDIA VOLUME CONTROL IN THE CYBER-PHYSICAL SYSTEM “SMART HOME” - ALEKSOV, SERHII; KOROBCHYNSKYI, MAKSYM (Herald of Khmelnytskyi National University. Technical sciences, 2025)
The main goal of the research was to develop and implement a decision-making method for fully automatic sound volume control in the Smart Home system. The need for such a subsystem is justified by the critical importance of ensuring an optimal microclimate and compliance with sanitary noise standards for the health, comfort and safety of residents. The developed method successfully solves this problem, ensuring that the multimedia volume level does not exceed the maximum levels established by law depending on the specific type of room and time of day. This is achieved by continuous (minute-by-minute) monitoring of the noise level using sensors and automatic comparison of the obtained data with predefined scenarios. The key advantage of the method is its full automaticity and flexibility of response. The system is able to accurately recognize three noise level states (optimal, high and unacceptably high), which makes it possible to apply appropriate measures - no action within the comfort range, warning the user when approaching the critical limit and forced automatic reduction of the volume to the maximum permissible level when the standards are violated. Such a differentiated response provides effective control aimed at preventing damage from excessive noise, while increasing the overall comfort of living. The experimental results confirmed the operability and adequacy of the developed method, demonstrating its ability to successfully respond to changes in noise levels in accordance with sanitary standards. At the same time, it was determined that the effectiveness of the method directly depends on the correctness of the initial settings (time and type of room) and the accuracy/sensitivity of the noise sensors used. In general, the study achieved its goal by implementing the necessary mechanism for automatic sound volume control, which is a significant step towards increasing the autonomy of cyber-physical systems "Smart Home".
Keywords: cyber-physical system; "Smart Home"; decision-making; multimedia volume control; noise level